PENGARUH AUTONOMOUS SENSORY MERIDIAN RESPONSE TERHADAP PENURUNAN STRES MAHASISWA YANG MENYUSUN SKRIPSI DI PROGRAM STUDI PSIKOLOGI UNIVERSTAS NEGERI MANADO - Deetje J. Solang; Sinta E. J. Kaunang; Euodia P. Legi (Program Studi Psikologi Universitas Negeri Manado, 2022)
This study aims to determine the effect of ASMR on reducing stress while writing thesis for students of Psychology Study Program, Manado State University. This research method uses quasi-experiments with the Time Series Design research design. The population of this study were 110 students of Psychology Study Program, Manado State University of class 2018. The subjects of this study were 22 students of class A. The data was collected with PSS-10 scale by Cohen & Williamson (1988) which was adapted by Purnami & Sawitri (2019) with 10 items. The results of the validity test on the instrument showed that 10 items were valid and the results of the reliability test of the instrument showed a coefficient value of 0,862. The research was tested using the Paired Sample T Test. The results showed that ASMR had an effect on reducing the stress in students who were writing thesis.